Innovative ICT-based Pedagogical Practices - Parra Bernal, Lina (2021)
This article presents the analysis of the innovative pedagogical practies mediated by ICT, carried out by the teachers of an educational institution in Popayán – Cauca, (Colombia). The research is qualitative, with a biographicl – narrative design, with a descriptive scope and developed through semi-structured interviesw applied to three teachers. The results allow establishing that teachers apply incremental innovation within the classroom, depending on the curricular needs and daily practice, buy they do not continuosly use Web 2.0 tools and Virtual Learning Environments, to articulate extra-class work; among the reason from this situation there are connectivity problems, resistance to change and poor institutional educational management.